FStream: Flexible Stream Scheduling and Prioritizing in Multipath-QUIC - Shi, Xiang; Wang, Lin; Zhang, Fa; Liu, Zhiyong (2019 IEEE 25th International Conference on Parallel and Distributed Systems (ICPADS), 2019)
While the web keeps evolving, web latency remains a major obstacle to improving user experience. In the past, many efforts have been made in this course. SPDY achieves reduced latency through multiplexing and prioritization by manipulating HTTP. Quick UDP Internet Connection (QUIC) generalizes the idea and embeds multiplexing in the transport layer by introducing application-oriented streams. Multipath-QUIC brings further improvements by utilizing multiple paths as is done in MultiPath TCP (MPTCP). However, failing to account for stream priorities in the transport layer can result in suboptimal performance for time-critical streams. We fill this gap and propose FStream - a flexible stream scheduling mechanism for Multipath-QUIC, which provides stream prioritization down to the transport layer. We implement FStream in Multipath-QUIC and demonstrate its effectiveness in reducing the completion time of time-critical streams (˜3x) through extensive experiments under different path dissimilarity conditions.